Experiences of a nutrition intervention—A qualitative study within a randomised controlled trial in men undergoing radiotherapy for prostate cancer. Issue 2 (27th June 2019) - Forslund, Marina; Nygren, Peter; Ottenblad, Anna; Johansson, Birgitta
Abstract: Aim: Men with prostate cancer undergoing radiotherapy may experience acute and late bowel symptoms. Nutrition interventions have shown some benefits, however, adherence tends to decline over time. Qualitative studies, carried out after an intervention, are important to help explain trial results. The aim of the present study was to explore patient experience of participating in a nutrition intervention in a randomised controlled trial, with a focus on facilitators and barriers to adherence. Methods: Semistructured interviews were conducted with 15 men with prostate cancer recruited from a randomised controlled trial on a nutrition intervention during radiotherapy. Interviews were analysed with content analysis with an inductive approach. Results: The informants were motivated to make dietary changes to avoid bowel symptoms. Social support, a feeling of contributing to the greater good, prior knowledge, dietary information and a small need for behaviour change facilitated adherence. Feeling limited, wanting to decide for themselves, the timing of the intervention, unmet expectations of dietary advice and loss of motivation, were described as barriers for adherence. Conclusions: Future nutrition intervention trials may benefit from involving significant others to a greater degree, as well as offering pre‐set recipes and strategies to manage social events, and more sessions with the dietitian for patients in need of more support. Tailored interventions based on the individual's preferences, context and prior knowledge about food may further facilitate adherence.